Happy Family Kitchen II: A Cluster Randomized Controlled Trial of a Community-Based Family Intervention for Enhancing Family Communication and Well-being in Hong Kong - Ho, Henry C. Y.; Mui, Moses; Wan, Alice; Ng, Yin-Lam; Stewart, Sunita M.; Yew, Carol; Lam, Tai Hing; Chan, Sophia S. (Frontiers in Psychology, 2016)
Long working hours and stressful urban lifestyles pose major challenges to family communication and well-being in Hong Kong. A community-based family intervention derived from a positive psychology framework, by using cooking and dining as a platform, was developed for improving family communication and well-being. Social workers and teachers from 31 social service units and schools in collaboration with an academic partner organized and conducted the intervention programs for 2,070 individuals from 973 families in a deprived district in Hong Kong. The participants were randomly assigned into the intervention or control group in a cluster randomized controlled trial (cRCT). The core intervention covered one of five positive psychology themes: joy, gratitude, flow, savoring, and listening. Assessments at pre-intervention, immediate post-intervention, and 4 and 12 weeks post-intervention showed improved family communication and well-being with sustainable effects up to 12 weeks. Positive changes in family happiness and family health were greater in the intervention group than in the control group. The savoring intervention had the most improved outcomes among the five themes. We concluded that this large-scale brief cRCT developed and conducted in real-world settings provided evidence for the feasibility and effectiveness of a community-based family intervention. This study was registered under ClinicalTrials.gov (NCT01796275).